Typical Japanese dietary pattern of meal consumption is positively related to healthy eating in university athletes - Daisuke Fujita; Kae Yanagisawa; Yuko Mekata; Kazuto Sasaki; Yukari Kawano (Japanese Society of Physical Fitness and Sports Medicine, 2020)
The aim of this study was to investigate the relationship between the frequency of typical Japanese dietary pattern (JDP) meal consumption and nutrient intake in Japanese university athletes. Dietary information was collected on three non-consecutive days using the 24-hour dietary recall method in the summer of 2013 and 2015. JDP meals were defined based on the Japanese Food Guide Spinning Top. A total of 272 (145 males) university athletes were divided into four groups based on their daily frequency of JDP meal consumption: daily consumption was ≤0.67 times in Group I (36 males, 57 females), once in Group II (39 males, 22 females), 1.33 times in Group III (35 males, 21 females), and ≥1.67 times in Group IV (35 males, 27 females). Logistic regression analysis was used to evaluate the odds ratio of not meeting the reference intake value of the dietary recommendation for athletes (DRA) or the recommended daily allowance for Japanese (2015) (RDA). The median JDP meal consumption was once a day. In both males and females, a significant trend was observed in energy intake, which progressively increased in Groups II, III, and IV compared to Group I (p < 0.001 for both genders). The higher the frequency of JDP meal consumption, the higher the intake of both food groups and nutrients. The higher the JDP meal frequency, the lower the risk of not meeting the DRA or RDA. These observations in summer suggest that increasing the frequency of JDP meal consumption may prevent inadequate nutrient intake for Japanese university athletes.